Alkyl pectin: Hydrophobic matrices for controlled drug release. Issue 3 (11th August 2014) - Zheng, Xue‐Fang; Lian, Qi; Yang, Hua; Zhu, Hong
ABSTRACT Alkyl pectin with various fatty acid (C4–C16) bromides increased its hydrophobic characteristic and made important changes in its structural features. Unmodified pectin exhibited a low degree of order (DO) and a weak tablet‐crushing strength. Pectin alkylated with a short chain length (C4) possessed similar properties but exhibited significant swelling. Alkylation with longer side chains (C8–C16) resulted in a higher DO and crushing strength but a lower swelling. The best mechanical characteristics and drug‐release properties were found for octanoyl pectin (OP; degree of substitution = 7.06–15.41%) tablets with 20% bovine serum albumin as a tracer. The high stability of these monolithic tablets appeared to be due to hydrophobic interactions between side chains, as shown by a more organized structure. IR spectroscopy and differential scanning calorimetry analyses of OP were consistent with a hydrophobic self‐assembling model. The drug dissolution kinetics showed longer release times for higher degrees of functionalization, that is, 35 h (for 10.88% substitution) and 80 h (for 15.41% substitution); this suggested OP excipients as interesting candidates for oral and subdermal pharmaceutical applications. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41302.